La stratégie discursive de Stephen Harper (2006-2010) - Denis Monière (Communication)
Does the position of a minority government influence the communication strategy of the party in power? To answer this question the author conducted a lexicometrical analysis of 302 official speeches pronounced by Stephen Harper, Prime Minister of Canada, from 2006 to 2010. The analysis of lexical indicators reveals that the lexical behaviours of Harper differ not only from those of leaders of past majority governments but also, in certain aspects, from those who led minority governments.